‘Let’s talk feelings’ podcast / Muhammad Heazry Amri Muhammad Azli and Dia Widyawati Amat - Muhammad Azli, Muhammad Heazry Amri; Amat, Dia Widyawati (Academy of Language Studies, 2023)
Our emotional, psychological, and social well-being are all parts of our mental health (What Is Mental, n.d.). It plays a role in influencing our thoughts, emotions, and behaviours. Additionally, it affects how we respond to stress, interact with others, and make decisions. Some of the effects that could happen are the weakening of immune system and exposure to substance abuse. Mills (2019) claimed that the immune system can suffer because of anxiety. A weak immune system can lead to various serious diseases that will result in serious health issues. Mills (2019) also reported that substance addiction is more likely to occur in people with mental illnesses. Unfortunately, people who are diagnosed with mental health illnesses avoid treatment due to society’s perception of mental health and a lack of information. Let's Talk Feelings is a podcast that aims to educate and raise awareness about mental health among its listeners. As a result, it will change society’s perception towards mental health and provide support to those dealing with mental health problems in a healthy and positive way.